Evaluation of relationship between QoS and QoE for web services considering the hierarchical structure with principal component analysis and path analysis - Koshimura, Ryosuke; Ito, Yoshihiro; Nomura, Yosuke (Asia-Pacific Conference on Communications (Print), 2014)
Since Quality of Experience of a Web service (Web-QoE) often deteriorates because of QoS degradation, it is essential to clarify relationship between QoE and QoS for the Web service. However, both QoS and QoE generally has multiple aspects each other. Consequently, the relationship is forced to be complex. This paper proposes a method of clarifying compound relationship between QoS and QoE, which adopts the path analysis and the principal component analysis. The authors performs their experiments with the proposed method, which are designated actual three Web services and utilize 29 subjects. The analytical results can clarify the complex relationship between QoE and QoS for Web services. Consequently, the effectiveness of the proposed method can be confirmed.